Lignin-furfural biomass-based phenolic resin and preparation method and application thereof

By reacting neutral or weakly alkaline eutectic solvents with lignin and furfural compounds, lignin-furfural biomass-based phenolic resins are prepared, which solves the problems of poor bonding performance of traditional phenolic resin adhesives and the introduction of harmful substances, and achieves a high bonding strength and green and environmentally friendly process.

CN116063643BActive Publication Date: 2025-04-11UNIV OF SCI & TECH OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310133180.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-08
Publication Date
2025-04-11
Estimated Expiration
2043-02-08

AI Technical Summary

Technical Problem

Traditional phenolic resin adhesives have problems with poor bonding properties, insufficient bonding strength, high industrial costs and introduction of harmful substances in wood bonding, especially with challenges in alternatives to phenol and formaldehyde.

Method used

A neutral or weakly basic eutectic solvent is used as a dispersant to prepare a lignin-furfural biomass-based phenolic resin by reacting with lignin and furfural compounds, thereby avoiding the use of phenol and formaldehyde.

Benefits of technology

The bonding strength and flame retardant and thermal insulation properties of lignin-furfural biomass-based phenolic resin are improved, and the production cost is reduced. The process is green and environmentally friendly and easy to be implemented in industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116063643B_ABST
    Figure CN116063643B_ABST
Patent Text Reader

Abstract

The present disclosure provides a lignin furfural biomass-based phenolic resin and its preparation method and application, which belongs to the technical field of phenolic resins. The preparation method of the lignin furfural biomass-based phenolic resin provided by the present disclosure includes: mixing choline chloride and at least one of urea or thiourea to form a neutral or weakly alkaline low eutectic solvent as a dispersant; adding a weakly alkaline potassium salt or sodium salt catalyst to the dispersant to form a multi-element low eutectic solvent; adding lignin to the multi-element low eutectic solvent and dispersing and depolymerizing to obtain a first mixture; adding a furfural compound to the first mixture for reaction to obtain a lignin furfural biomass-based phenolic resin; wherein the weakly alkaline potassium salt catalyst includes: potassium carbonate, potassium bicarbonate; the weakly alkaline sodium salt catalyst includes sodium bicarbonate. The phenolic resin prepared by the present disclosure is phenol-free and formaldehyde-free, and can be used for wood product processing, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of phenolic resins, and in particular to a lignin-furfural biomass-based phenolic resin and a preparation method and application thereof. Background Art

[0002] Phenolic resin adhesives are widely used in industry and have excellent performance in wood bonding. Traditional phenolic resin adhesives are mainly made by reacting phenol and formaldehyde. The prepared resin adhesives have certain toxicity. Moreover, phenol and formaldehyde are both derived from petroleum resources. They are not only highly toxic, but also costly. In the current environment of scarce petroleum resources, it is necessary to find suitable good substitutes for phenol and formaldehyde.

[0003] In order to solve these problems, the related art uses lignin containing rich phenolic hydroxyl structures as a substitute for phenol, and furfural extracted from biomaterials as a substitute for formaldehyde. However, the phenolic resin prepared in the related art mainly uses lignin to replace part of phenol, or uses furfural to partially replace formaldehyde to synthesize bio-based phenolic resin. Most of the synthesis processes use NaOH as a dispersant. The phenolic resin adhesive obtained by this method has the problem of poor bonding performance. Moreover, when the amount of lignin added is high, the bonding strength of the adhesive is significantly reduced, which cannot meet the practical requirements. At the same time, the addition of phenol also increases industrial costs and introduces harmful substances. Summary of the invention

[0004] In view of the above technical problems, the present disclosure provides a lignin-furfural biomass-based phenolic resin and a preparation method and application thereof, in order to at least partially solve at least one of the above-mentioned technical problems.

[0005] As one aspect of the present disclosure, a method for preparing a lignin-furfural biomass-based phenolic resin is provided, comprising the following steps:

[0006] mixing choline chloride and at least one of urea or thiourea to form a neutral or weakly alkaline deep eutectic solvent as a dispersant;

[0007] A weakly alkaline potassium salt or sodium salt catalyst is added to the dispersant to form a multi-element deep eutectic solvent;

[0008] Adding lignin to the multi-element low eutectic solvent to disperse and depolymerize the lignin to obtain a first mixture;

[0009] adding a furfural compound to the first mixture to react and obtain a lignin-furfural biomass-based phenolic resin;

[0010] Among them, the weakly alkaline potassium salt catalyst includes: potassium carbonate, potassium bicarbonate; the weakly alkaline sodium salt catalyst includes: sodium bicarbonate.

[0011] As another aspect of the present disclosure, provided is a lignin-furfural biomass-based phenolic resin prepared by the method as described above.

[0012] As another aspect of the present disclosure, provided is the use of the above-mentioned lignin-furfural biomass-based phenolic resin as an adhesive.

[0013] Based on the above technical solution, the lignin-furfural biomass-based phenolic resin provided by the present disclosure and its preparation method and application include at least one of the following beneficial effects:

[0014] (1) In the embodiments of the present disclosure, choline chloride is first eutectic with urea or thiourea providing a hydrogen bond donor to form a stable hydrogen bond to obtain a neutral or weakly alkaline low eutectic solvent as a dispersant, and then a weakly alkaline potassium salt or sodium salt catalyst is added and mixed to form a multi-element low eutectic solvent, wherein the weakly alkaline potassium salt or sodium salt is used as a catalyst for the lignin-furfural compound reaction, mainly for providing an alkaline environment; the neutral or weakly alkaline low eutectic solvent (choline chloride + urea / thiourea) is selected as a dispersant to provide a stable reaction environment for the dispersion and depolymerization of lignin. Then, lignin is added to a multi-component low eutectic solvent for dispersion and depolymerization to obtain a first mixture (i.e., a multi-component low eutectic solvent-lignin mixed solution); then, furfural compounds are added to the first mixture, and the ortho-para positions of the phenolic hydroxyl groups in the lignin react with the aldehyde groups of the furfural compounds to undergo nucleophilic addition reactions to generate ortho- and para-hydroxymethylphenols, and under alkaline conditions, the hydroxymethyl groups condense with active hydrogens on other benzene rings to form a polyphenol alcohol bridged by a methylene group, and then an addition polycondensation reaction is carried out to form a phenolic resin, and the obtained phenolic resin does not contain harmful substances such as formaldehyde and phenol, and has the characteristics of being green and environmentally friendly.

[0015] (2) In the embodiments disclosed herein, a neutral or weakly alkaline low eutectic solvent is used as a dispersant, which can reduce the damage of the solvent to the lignin structure and can also allow lignin and furfural compounds to react in a homogeneous phase, and the reaction is relatively complete. In addition, the method disclosed in the embodiments of the present invention is a one-pot method for preparing lignin-furfural biomass phenolic resin, which is simple and efficient to operate, produces less three wastes, and is easy to industrialize. In addition, no toxic and harmful substances such as phenol and formaldehyde are introduced during the preparation process, which is a green and environmentally friendly phenolic resin processing technology.

[0016] (3) In the embodiments of the present disclosure, the lignin and furfural in the raw materials are both derived from biomass raw materials, which are low-cost, simple and easy to obtain. At the same time, the introduction of substances such as phenol and formaldehyde is avoided, and the product is more green and environmentally friendly.

[0017] (4) In the embodiments of the present disclosure, the prepared lignin-furfural biomass-based phenolic resin adhesive has a strong bonding strength to wood, and has a stronger bonding strength at low temperatures (below -30°C), and also has flame retardant and heat insulating properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 A schematic diagram of the bonding strength of the phenolic resin adhesive prepared in Example 1 of the present disclosure at 25°C and -30°C;

[0019] Figure 2 Schematic diagram of testing the thermal insulation performance of the phenolic resin adhesive prepared in Example 1 of the present disclosure. DETAILED DESCRIPTION

[0020] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in conjunction with specific embodiments.

[0021] At present, phenolic resin adhesives are widely used in industry, especially in wood product processing, such as the furniture market. However, the raw materials phenol and formaldehyde for preparing phenolic resins are not only expensive, but also pollute the environment and are toxic and harmful to the human body.

[0022] In the related art research, because the activity of phenolic hydroxyl in lignin is not as good as phenol, when lignin is used to prepare lignin-furfural resin adhesive, lignin needs to be modified. At present, the preparation of lignin-furfural phenolic resin adhesive is not to replace all phenol with lignin, but to modify lignin or disperse lignin with a dispersant, and then react with furfural. For example, lignin is modified by methoxy or hydroxymethylation, or sodium hydroxide and ionic liquid are used as dispersants to depolymerize and modify lignin, so as to increase the activity of phenolic hydroxyl in lignin. However, in the process of dispersion, the alkalinity of NaOH solution is too strong when used as a dispersant, and the corrosive effect on lignin is too large, which destroys the structure of lignin, so that lignin is not fully reacted with the aldehyde group in furfural or formaldehyde, resulting in the preparation of partial lignin instead of phenol. The bonding strength of the phenolic resin adhesive is small, and there are still some phenol and formaldehyde residues in the obtained phenolic resin.

[0023] In view of this, the present disclosure proposes a method for preparing a lignin-furfural biomass-based phenolic resin using a one-pot method using a low eutectic solvent, wherein lignin completely replaces phenol and furfural completely replaces formaldehyde, wherein a neutral or weakly alkaline low eutectic solvent is selected as a depolymerization and dispersant of lignin, and after the lignin is depolymerized and dispersed, the multi-element low eutectic solvent is retained in the system to participate in the preparation process of the phenolic resin system. By controlling the amount of the multi-element low eutectic solvent, the bonding performance and flame retardant performance of the prepared lignin-furfural biomass-based phenolic resin adhesive can be enhanced.

[0024] According to an embodiment of the present disclosure, a method for preparing a lignin-furfural biomass-based phenolic resin is provided, comprising:

[0025] mixing choline chloride and at least one of urea or thiourea to form a neutral or weakly alkaline deep eutectic solvent as a dispersant;

[0026] A weakly alkaline potassium salt or sodium salt catalyst is added to the dispersant to form a multi-element deep eutectic solvent;

[0027] adding lignin to a multi-element low eutectic solvent for dispersion and depolymerization to obtain a first mixture;

[0028] adding a furfural compound to the first mixture to react and obtain a lignin-furfural biomass-based phenolic resin;

[0029] Among them, weakly alkaline potassium salt catalysts include: potassium carbonate, potassium bicarbonate; weakly alkaline sodium salt catalysts include: sodium bicarbonate.

[0030] Before the experiment, a certain screening was carried out on the selection of catalysts and dispersants, such as sodium hydroxide, sodium carbonate, potassium hydroxide, potassium carbonate, potassium bicarbonate, sodium bicarbonate and other catalysts. The experiment showed that when sodium hydroxide, sodium carbonate and potassium hydroxide were used as catalysts, the performance of the phenolic resin adhesive obtained was not as good as potassium carbonate. The main reason is that the alkalinity of potassium hydroxide and sodium hydroxide is too strong, which may damage the structure of lignin. Sodium carbonate cannot form a multi-element low eutectic solvent with choline chloride and urea, resulting in it not participating in the reaction and not placing the reaction system in an alkaline environment, resulting in poor bonding performance of the prepared phenolic resin adhesive. Therefore, in the embodiments of the present disclosure, it is preferred that a weakly alkaline potassium salt or sodium salt catalyst and a neutral or weakly alkaline low eutectic solvent form a multi-element low eutectic solvent, wherein the weakly alkaline potassium salt or sodium salt is used as a catalyst for the reaction of lignin-furfural compounds, mainly for providing an alkaline environment; a neutral or weakly alkaline low eutectic solvent is selected as a dispersant to provide a stable reaction environment for the dispersion and depolymerization of lignin, wherein the neutral or weakly alkaline low eutectic solvent can be obtained by eutecticizing choline chloride with urea or thiourea providing a hydrogen bond donor and forming a stable hydrogen bond.

[0031] Add lignin to a polynary low eutectic solvent for dispersion and depolymerization to obtain a first mixture (i.e., a polynary low eutectic solvent-lignin mixed solution); then add furfural compounds to the first mixture, and the ortho-para positions of the phenolic hydroxyl groups in the lignin react with the aldehyde groups of the furfural compounds to undergo nucleophilic addition reactions to generate ortho- and para-hydroxymethylphenols. Under alkaline conditions, the hydroxymethyl groups condense with active hydrogens on other benzene rings to form polyphenol alcohols bridged by methylene groups, which are then subjected to addition polycondensation reactions to form phenolic resins. When a neutral or alkaline low eutectic solvent is used as a dispersant, the damage to the lignin structure can be reduced and lignin and furfural compounds can be homogeneously reacted, and the reaction is relatively complete. In addition, the present disclosure adopts a one-pot method to prepare lignin-furfural biomass phenolic resins, which is simple to operate, efficient, produces less three wastes, and is easy to industrialize. In the preparation process, no toxic and harmful substances such as phenol and formaldehyde are introduced, and it is a green and environmentally friendly phenolic resin processing technology.

[0032] Preferably, the molar ratio of choline chloride to urea or thiourea in the neutral or weakly alkaline low eutectic solvent is 1:1-3. The amount of potassium salt or sodium salt catalyst added accounts for 1%-3% of the amount of dispersant for choline chloride and urea or thiourea, for example, it can be 1%, 2%, 3%, and more preferably 2% of the dispersant. Relevant preliminary experiments show that only when the amount of sodium salt or potassium salt catalyst is less than 3%, it can form a multi-element low eutectic solvent with choline chloride and urea / thiourea. When the sodium salt or potassium salt catalyst exceeds 3%, it cannot be doped into the dispersant, and thus a multi-element low eutectic solvent cannot be formed. In addition, in the process of forming the multi-element low eutectic solvent, it is necessary to first add the catalyst after choline chloride forms a stable hydrogen bond with urea or thiourea, so as to ensure that choline chloride and urea or thiourea can form a stable hydrogen bond.

[0033] According to an embodiment of the present disclosure, the parameters for adding lignin to the multi-component deep eutectic solvent to form the first mixture include:

[0034] Add lignin to the multi-component low eutectic solvent, and stir the reaction at 80-100°C for 10-14h to obtain a first mixture, i.e., a lignin-multi-component low eutectic solvent mixed solution. The heating and stirring at 80-100°C is to accelerate the dispersion and depolymerization of lignin in the multi-component low eutectic solvent. The depolymerized lignin is retained in the multi-component low eutectic solvent, exposing more active sites of the lignin, in preparation for the next step of the phenolic condensation reaction with the furfural compound.

[0035] According to an embodiment of the present disclosure, the parameters for adding the furfural compound to the first mixture to obtain the lignin-furfural biomass-based phenolic resin through reaction include:

[0036] Furfural compounds are added to the first mixture, and the mixture is stirred at 80-100°C for 20-40 minutes, and then the reaction temperature is raised to 110-130°C and stirred for 5-7 hours to obtain lignin-furfural biomass-based phenolic resin. The purpose of raising the temperature to 80-100°C is to allow the furfural compounds to fully contact and mix with the depolymerized lignin, and then further raise the temperature to 110-130°C to allow the ortho-para positions of the phenolic hydroxyl groups to fully react with the aldehyde groups in the furfural compounds to generate ortho- and para-hydroxymethylphenols. The multi-element low eutectic solvent provides conditions for homogeneous reaction of lignin and furfural compounds, making the reaction more complete and further alleviating the local polymerization of lignin and furfural compounds.

[0037] According to the embodiments of the present disclosure, the sources of lignin and furfural compounds include: straw, rice husk, corn cob. Biomass raw materials such as straw, rice husk, corn cob, bamboo powder, etc. are rich in lignin, cellulose and hemicellulose, and furfural is a chemical product. It is hydrolyzed into pentose (monosaccharide) by high-polymer bran (cellulose, hemicellulose) in plant fiber raw materials under a certain temperature and catalyst. The pentose is then dehydrated to generate furfural. The furfural compounds in the embodiments of the present disclosure are mainly extracted from biomass. Therefore, the raw materials of lignin and furfural compounds in the embodiments of the present disclosure are simple and easy to obtain, low in cost, non-toxic and harmless, and are green and environmentally friendly biomass raw materials.

[0038] According to the embodiments of the present disclosure, the furfural compounds include any one of the following: furfural, 5-hydroxymethyl-furfural. The reaction mechanism of the synthesis of phenolic resin is the polymerization reaction of phenol and aldehyde. In theory, most furfural compounds can be used. In the embodiments of the present disclosure, furfural and 5-hydroxymethyl-furfural are preferred, mainly because the toxicity of this furfural compound is low, it is green and environmentally friendly, and the cost of use is low. In addition, the activity of the aldehyde group in furfural and 5-hydroxymethyl-furfural is strong, and the performance of the obtained phenolic resin is relatively good, which is more suitable for use as a raw material for furfural reactions; while for furfural with lower aldehyde group activity, the performance of the obtained phenolic resin is slightly poor.

[0039] According to the embodiments of the present disclosure, the mass ratio of the multi-component low eutectic solvent, lignin and furfural compounds is: 2: 0.9-1.1: 0.6-0.9. If the amount of the multi-component low eutectic solvent is too small, the lignin cannot be completely depolymerized and dispersed, thereby inducing local polymerization of lignin and the multi-component low eutectic solvent; if the amount of the multi-component low eutectic solvent is too much, the entire system will be diluted, the viscosity of the phenolic reaction system will be reduced, the subsequent heating reaction time will be prolonged, and the adhesive properties of the phenolic resin product will be affected. Therefore, when the mass ratio of the multi-component low eutectic solvent to lignin is close to 2: 1, the obtained phenolic resin adhesive has better performance.

[0040] According to an embodiment of the present disclosure, a lignin-furfural biomass-based phenolic resin is also provided, which is prepared by the preparation method in the above embodiment. The prepared lignin-furfural biomass-based phenolic resin is free of phenol and formaldehyde, and the raw materials are easily available, safe and stable.

[0041] According to an embodiment of the present disclosure, an application of using lignin-furfural biomass-based phenolic resin as an adhesive is also provided. In the related art, phenolic resin adhesives are generally hot-pressed under the conditions of 120°C-150°C and 1.3-1.6MPa, while in the present disclosure, the provided lignin-furfural biomass-based phenolic resin adhesive can be hot-pressed at 120°C and 0.13Mpa, which is more energy-saving and environmentally friendly than the hot-pressing conditions in the related art.

[0042] According to the embodiments of the present disclosure, the bonding strength of the lignin-furfural biomass-based phenolic resin adhesive is 3.9-4.54 MPa at 20-35°C; and 5.0-5.5 MPa below -30°C.

[0043] In the embodiments of the present disclosure, the lignin-furfural biomass-based phenolic resin adhesive provided by the present disclosure has strong bonding strength to wood, and has stronger bonding strength at low temperatures, and also has flame retardant and heat insulating properties, is non-toxic and harmless, and is especially used as a safe, reliable and stable adhesive in furniture and industry. It can improve the quality of adhesives used in wood, has good economic and social benefits, and has broad market prospects. In addition, the bonding strength of the lignin-furfural biomass-based phenolic resin adhesive provided by the present invention is much higher than the national requirement standard for phenolic resin wood adhesives, which is a bonding strength ≥0.7MPa (GB / T14732-2017), and is comparable to the bonding strength of traditional phenol-formaldehyde phenolic resin of 4.6MPa, and is also higher than the bonding strength of lignin-formaldehyde phenolic resin adhesive (4MPa). The main reason is that the lignin-furfural biomass-based phenolic resin adhesive provided by the present invention contains a multi-low eutectic solvent, which can destroy wood cellulose and lignin without causing corrosion. After heating treatment, the adhesive can better penetrate into the interior of the wood, so it has excellent bonding properties.

[0044] The present disclosure is further described below by comparative examples, embodiments, drawings and related test experiments and results thereof. In the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present disclosure. However, it is apparent that one or more embodiments may also be implemented without these specific details. Moreover, in the absence of conflict, the details in the following embodiments may be arbitrarily combined into other feasible embodiments.

[0045] It should be noted that the following specific examples are only for illustration, and the protection scope of the present disclosure is not limited thereto. The chemicals and raw materials used in the following examples are all commercially available or prepared by recognized preparation methods.

[0046] Example 1

[0047] Preparation of phenolic resin adhesive: First, weigh choline chloride and urea according to the molar ratio of choline chloride to urea of ​​1:1, then mix the two at 70°C, add 1% anhydrous potassium carbonate, and then stir at 70°C for 20 to 40 minutes to obtain a clear and transparent multi-element low eutectic solvent. Add lignin while stirring the multi-element low eutectic solvent, then heat to 80°C and stir for 12 hours to disperse and depolymerize the lignin. Then, add furfural to the multi-element low eutectic solvent-lignin mixture and stir at 90°C for 20 to 40 minutes to fully mix the multi-element low eutectic solvent, lignin and furfural reactants, then heat to 120°C and react for 6 hours to obtain a lignin-furfural biomass-based phenolic resin adhesive, wherein the mass ratio of the multi-element low eutectic solvent, lignin and furfural in the reaction system is 2:0.9:0.6.

[0048] Furthermore, the bonding performance, flame retardancy and thermal insulation performance of the lignin-furfural biomass-based phenolic resin adhesive obtained in Example 1 were tested, and the specific test process is as follows:

[0049] 1) Sample treatment: Take 0.1 g of the phenolic resin adhesive prepared in Example 1 and apply it on one-third (10×10 mm 2 ) on a Paulownia wood sample (10mm×30mm×2mm). Place a portion of the coated sample in a muffle furnace, press an iron block on top of the sample, and hot press the sample at 0.1-0.15MPa, 120-150℃ for 10-30min, then slowly cool to room temperature, and continue cold pressing for 10-14h.

[0050] 2) Room temperature (25°C) bonding performance test: The cold-pressed samples were placed at room temperature (25°C) for 10-14 hours, and then the samples were subjected to an adhesion performance test using a tensile machine at a speed of 5 mm / min. The bonding strength was recorded as the maximum tensile strength.

[0051] 3) Low temperature (-30°C) bonding performance test: The cold-pressed samples were placed at -30°C for 10-14 hours, and then the bonding performance of the samples was tested using a tensile machine at a speed of 5 mm / min. The bonding strength was recorded as the maximum tensile strength.

[0052] Figure 1 It is a schematic diagram of the bonding strength of the lignin-furfural biomass-based phenolic resin adhesive prepared in Example 1 of the present disclosure at 25°C and -30°C.

[0053] like Figure 1 As shown in the figure, the lignin-furfural phenolic resin has a strong bonding strength, which can reach 4.54MPa at room temperature 25°C, and even at -30°C, the bonding strength of the lignin-furfural phenolic resin can reach 5.3MPa, far exceeding the bonding strength required by the national regulations for phenolic resin wood adhesives GB / T 14732-2017 (≥0.7MPa), where Figure 1 The 0.13MPa in the figure represents that the hot pressing pressure of the lignin-furfural phenolic resin adhesive is 0.13MPa. In addition, the bonding strength of the lignin-furfural phenolic resin adhesive provided by the present disclosure can reach 3.9MPa in an environment of about 35°C, indicating that the lignin-furfural phenolic resin adhesive provided by the present disclosure meets the application needs of daily life.

[0054] Flame retardant experiment: prepare two identical pieces of Paulownia wood, one side of which is coated with lignin-furfural phenolic resin adhesive, and the other is not treated, then the side coated with lignin-furfural phenolic resin adhesive and the side not treated are placed on an alcohol lamp for about 10 seconds, it can be found that the Paulownia wood piece without any treatment burns, while the Paulownia wood piece coated with phenolic resin adhesive does not burn, the main reason is that the surface of the Paulownia wood piece coated with lignin-furfural phenolic resin adhesive will carbonize to form a thin carbon layer, which can ensure that the inside of the Paulownia wood piece will not burn. Therefore, it is concluded that the lignin-furfural phenolic resin adhesive provided by the present disclosure has flame retardant properties.

[0055] Thermal insulation experiment: Take two identical paulownia wood chips, marked as paulownia wood chip A and paulownia wood chip B, one side of paulownia wood chip A is coated with lignin-furfural phenolic resin adhesive, and paulownia wood chip B is not treated in any way. Then, the side of paulownia wood chip A coated with phenolic resin adhesive and the side of paulownia wood chip B that has not been treated are placed on an alcohol lamp for about 10 seconds, and the back temperature of paulownia wood chip A and paulownia wood chip B is tested using an infrared thermal imager.

[0056] Figure 2 Schematic diagram of testing the thermal insulation performance of the phenolic resin adhesive prepared in Example 1 of the present disclosure.

[0057] like Figure 2 As shown, the back temperature of the Paulownia wood piece B exceeds 300° C., while the back temperature of the Paulownia wood piece A is only about 100° C., indicating that the lignin-furfural phenolic resin adhesive provided by the present disclosure has excellent thermal insulation properties.

[0058] Example 2

[0059] Preparation of phenolic resin adhesive: First, weigh choline chloride and urea according to the molar ratio of choline chloride to urea of ​​1:3, then mix the two at 90°C, add 3% anhydrous sodium carbonate thereto, and then stir at 90°C for 20 to 40 minutes to obtain a clear and transparent multi-element low eutectic solvent. Add lignin while stirring the multi-element low eutectic solvent, then heat to 100°C and stir for 12 hours to disperse and depolymerize the lignin. Then, add furfural to the multi-element low eutectic solvent-lignin and stir at 100°C for 20 to 40 minutes to fully mix the multi-element low eutectic solvent, lignin and furfural reactants, then heat to 120°C and react for 6 hours to obtain a lignin-furfural biomass-based phenolic resin adhesive, wherein the mass ratio of the multi-element low eutectic solvent, lignin and furfural in the system is 2:1.1:0.9.

[0060] Example 3

[0061] Preparation of phenolic resin adhesive: First, weigh choline chloride and urea according to the molar ratio of choline chloride to urea of ​​1:2, then mix the two at 80°C, add 2% anhydrous potassium bicarbonate thereto, and then stir at 80°C for 20-40 minutes to obtain a clear and transparent multi-element low eutectic solvent. Add lignin while stirring the multi-element low eutectic solvent, then heat to 90°C and stir for 12 hours to disperse and depolymerize the lignin. Then, add 5-hydroxymethylfurfural to the multi-element low eutectic solvent-lignin mixture and stir at 90°C for 20-40 minutes to fully mix the multi-element low eutectic solvent, lignin and furfural reactants, then heat to 120°C and react for 6 hours to obtain a lignin-furfural biomass-based phenolic resin adhesive, wherein the mass ratio of the multi-element low eutectic solvent, lignin and furfural in the reaction system is 2:0.9:0.6.

[0062] Example 4

[0063] Preparation of phenolic resin adhesive: First, 4.8-5.2g of choline chloride and 4.1-4.5g of thiourea are weighed according to the molar ratio of choline chloride to thiourea of ​​1:2, and then the two are mixed at 80°C, and then 2% of anhydrous potassium carbonate is added to the mixed solution of choline chloride and thiourea, and then stirred at 80°C for 20-40min to obtain a clear and transparent multi-element low eutectic solvent. 4-6g of lignin is added while the multi-element low eutectic solvent is stirred, and then the mixed system containing the multi-element low eutectic solvent and lignin is heated to 90°C, and the mixed system is fully stirred for 12h to disperse and depolymerize the lignin. Then, 3-4.5 g of furfural is added to the multi-component low eutectic solvent-lignin and stirred at 90°C for 20-40 min to fully mix the multi-component low eutectic solvent, lignin and furfural reactant, and then the temperature is raised to 120°C and reacted for 6 hours to obtain a lignin-furfural phenolic resin adhesive, wherein the mass ratio of the multi-component low eutectic solvent, lignin and furfural in the multi-component low eutectic solvent-lignin-furfural system is 2:1:0.75.

[0064] The above-mentioned Examples 2 to 4 use the same method as in Example 1 to test the bonding strength, flame retardancy and thermal insulation properties of the lignin-furfural phenolic resin adhesive. The relevant test results show that the bonding strength of the adhesive obtained by the method in Examples 2-4 is slightly lower than the bonding strength of Example 1, but higher than the bonding strength required by the national regulations for phenolic resin wood adhesives GB / T 14732-2017 (≥0.7MPa), and the lignin-furfural phenolic resin adhesive prepared by the method in Examples 2-4 still has similar flame retardancy and thermal insulation properties as Example 1.

[0065] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present disclosure. It should be understood that the above description is only a specific embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.

Claims

1. A method for preparing a lignin-furfural biomass-based phenolic resin, comprising: mixing choline chloride and at least one of urea or thiourea to form a neutral or weakly alkaline deep eutectic solvent as a dispersant; adding a weakly alkaline potassium salt or sodium salt catalyst to the dispersant to form a multi-element deep eutectic solvent; Adding lignin to the multi-element low eutectic solvent to disperse and depolymerize the lignin to obtain a first mixture; adding a furfural compound to the first mixture to react and obtain a lignin-furfural biomass-based phenolic resin; Wherein, the weakly alkaline potassium salt catalyst includes: potassium carbonate, potassium bicarbonate; the weakly alkaline sodium salt catalyst includes: sodium bicarbonate; Among them, the molar ratio of choline chloride to urea or thiourea is 1:1-3; the added amount of the potassium salt or sodium salt catalyst accounts for 1%-3% of the amount of the dispersant; the mass ratio of the multi-element low eutectic solvent, lignin and furfural compounds is: 2:0.9-1.1:0.6-0.

9.

2. The method according to claim 1, wherein: The parameters for adding the lignin to the multi-component deep eutectic solvent to form the first mixture include: The reaction was stirred at 80-100° C. for 10-14 h to obtain the first mixture.

3. The method according to claim 1, wherein: The parameters for adding the furfural compound to the first mixture to obtain the lignin-furfural biomass-based phenolic resin through reaction include: The furfural compound is added to the first mixture, and the mixture is stirred and reacted at 80-100° C. for 20-40 minutes, and then the reaction temperature is increased to 110-130° C. and stirred and reacted for 5-7 hours to obtain a lignin-furfural biomass-based phenolic resin.

4. The method according to claim 1, wherein: The furfural compound includes any one of the following: Furfural, 5-hydroxymethyl-furfural.

5. The method according to claim 1, wherein: The sources of the lignin and furfural compounds include straw, rice husk, corn cob and bamboo powder.

6. A lignin-furfural biomass-based phenolic resin, prepared by the method according to any one of claims 1 to 5.

7. Use of the lignin-furfural biomass-based phenolic resin according to claim 6 as an adhesive.

8. The use according to claim 7, wherein: The adhesive has a bonding strength of 3.9-4.54 MPa at 20-35°C; The adhesive has a bonding strength of 5.0-5.5 MPa at a temperature below -30°C.

Citation Information

Patent Citations

  • Method for preparing biomass polyurethane based on high-activity lignin polyphenol and product

    CN113861364A

  • Method for efficiently pretreating corncobs by using ultrasonic-assisted ternary eutectic solvent

    CN114891844A